Gangs in the El Paso-Juárez borderland: the role of history and geography in shaping criminal subcultures - Tapia, Mike (Trends in organized crime, 2020)
This paper examines the early precursors of organized criminal subcultures using the U.S.-Mexico border city of El Paso, Texas as a case-study. El Paso is known as the birthplace of the pachuco; the Mexican Americans’ original street-oriented subculture. It formed the basis for the numerous delinquent groups that would emerge there throughout the decades, ultimately producing a binational organized crime syndicate called the Barrio Azteca. This barrio-prison-cartel hybrid is a modern group with deep roots in the street-gang subcultures of the region. The current study shows that its ties to drug gangs in Ciudad Juárez and subsequent federal prosecutions were recent catalysts in its escalation as a unique cross-border entity. The work is informed by archival material, police data, and multi-faceted fieldwork with gang members and police. It illustrates how the El Paso-Juárez metroplex has fostered particular criminological dynamics not seen in any other place in the U.S. to date.